Thermal analysis of Co-Zn ferrite synthesis from milled powders - Nikolaev E. V. Evgeny Vladimirovich; Lysenko E. N. Elena Nikolaevna; Surzhikov A. P. Anatoly Petrovich; Astafjev A. L. Aleksandr Leonidovich (2023, 2023)
Title screen